Answer:
x =(6+√-4)/4=(3+i)/2= 1.5000+0.5000i
Explanation:
Equation at the end of step 1 :
(2x2 - 6x) + 5 = 0
Step 2 :
Trying to factor by splitting the middle term
2.1 Factoring 2x2-6x+5
The first term is, 2x2 its coefficient is 2 .
The middle term is, -6x its coefficient is -6 .
The last term, "the constant", is +5
Step-1 : Multiply the coefficient of the first term by the constant 2 • 5 = 10
Step-2 : Find two factors of 10 whose sum equals the coefficient of the middle term, which is -6 .
-10 + -1 = -11
-5 + -2 = -7
-2 + -5 = -7
-1 + -10 = -11
1 + 10 = 11
2 + 5 = 7
5 + 2 = 7
10 + 1 = 11
It's a lot i know but if it is wrong i'm very sorry please don't come at me wrong!